Radical democratic thought and contemporary American public administration: a substantive perspective - Ventriss, Curtis (1998)
This article argues that radical democratic thought, although to a large extent theoretically ignored in public administration, has an important role to play in raising critical issues that are interwoven with the political and economic fabric of society itself. Specifically, it contends that radical thought challenges the field to reconceptualize the role of democratic citizenship in a modern polity and to rethink the theoretical and intellectual development of public administration theory. - Reproduced
Keywords: Public administration - United States; Public administration